2009
DOI: 10.1021/np900160g
|View full text |Cite
|
Sign up to set email alerts
|

Mansouramycins A−D, Cytotoxic Isoquinolinequinones from a Marine Streptomycete

Abstract: Chemical screening of the ethyl acetate extract from the marine-derived Streptomyces sp. isolate Mei37 resulted in five isoquinolinequinones, four new derivatives, mansouramycin A-D (1, 3-5), and the known 3-methyl-7-(methylamino)-5,8-isoquinolinedione (2). Their structures were elucidated by NMR and MS techniques and by comparison with related compounds. Cytotoxicity profiling of the mansouramycins in a panel of up to 36 tumor cell lines indicated significant cytotoxicity of several derivatives, with pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 23 publications
(30 reference statements)
5
76
0
Order By: Relevance
“…Several similar novel isoquinoline alkaloids have been reported from the genus of Penicillium, 17 Aspergillus, 18 Streptomyces 19,20 and Chaetomium. 21 Most isoquinoline alkaloids discovered from plants exhibit complicated structures, which were mainly synthesized from tyrosine, whereas most isoquinolines from lichens, fungi, and sponges show simple skeletons and are probably biosynthesized via mixed pathways.…”
Section: Resultsmentioning
confidence: 82%
“…Several similar novel isoquinoline alkaloids have been reported from the genus of Penicillium, 17 Aspergillus, 18 Streptomyces 19,20 and Chaetomium. 21 Most isoquinoline alkaloids discovered from plants exhibit complicated structures, which were mainly synthesized from tyrosine, whereas most isoquinolines from lichens, fungi, and sponges show simple skeletons and are probably biosynthesized via mixed pathways.…”
Section: Resultsmentioning
confidence: 82%
“…In vitro cytotoxicity against several human cancer cell lines such as MDA-MB-231, HCT 15, human prostate cancer (PC-3), human lung cancer (NCI-H23), human renal cancer (ACHN), human skin cancer (LOXIMVI), K562 proved that streptokordin exhibited significant cytotoxicity (Jeong et al 2006). Hawas et al (2009) reported the isolation of Streptomyces sp. Mei37 from the muddy sediment of Jade Bay on the southern German North Sea coast, which produced five isoquinolinequinones among which mansouramycin C as the main quinone.…”
Section: Indolocarbazolesmentioning
confidence: 99%
“…Mansouramycin C dark red in color, showed highest cytotoxic action compared with other mansouramycis. When tested on 36 different cancer cell lines it exhibited action against 10 cell lines (T-24, SF-268, LXFA629L, MEXF 520L, OVCAR-3, RXF944L and UXF1138L), with inhibition concentrations ranging from 0.008 to 0.02 µM (Hawas et al 2009). Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…Mansouramycins A-D are isoquinolinequinones isolated from the marine-derived Mei37 isolate of Streptomyces sp. They show antitumour activity against lung cancer, breast cancer, melanoma and prostate cancer cells [11,75]. Tartrolons, compounds leukaemia cell line K562), antiprotozoal and free radical scavenging activity (Figure 9) [78].…”
Section: Anticancer Activity Of Actinomycete Metabolites Now and In mentioning
confidence: 99%